Pengaruh Model Pembelajaran Project Based Learning dengan Pendekatan Respect Education terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Ekonomi - Pebriyanti Habibu; Roy Hasiru; Abdulrahim Maruwae (Jurnal Pendidikan Dirgantara, 2025)
The purpose of this study was to determine whether the project based learning model with the respect education approach can improve students' critical thinking skills in the subject of economics for class XI at Sma Negeri 2 Tilamuta. This study used a quantitative approach with a quasi-experimental research design (quasi-experiment) with a sample size of 61 students. The data collection techniques used in this study were observation, tests, documentation and research data were analyzed descriptively and inferentially with the t-test. The results showed that the critical thinking skills of students who used the Project Based Learning Model with the Respect Education Approach increased more than students who used the Conventional Learning Model in the Subject of Economics for Class XI at Sma Negeri 2 Tilamuta. This is supported by the independent sample test, the results of the t-test showed a sig. (2-tailed) value of 0.021 (p <0.05), which means that there is a significant difference between the experimental group and the control group in terms of students' critical thinking skills